PENYERANGAN TERHADAP PASIEN DI RUMAH SAKIT IBN SINA TEPI BARAT PALESTINA OLEH TENTARA ISRAEL DENGAN PENYAMARAN SEBAGAI DOKTER: ATTACKS ON PATIENTS AT IBN SINA HOSPITAL ON THE WESTBANK PALESTINE COMMITTED BY ISRAELI SOLDIERS DISGUISED AS DOCTORS - Dzuhria, Ade Rizky; Wibowo, Aji (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2023)
The purpose of this research is to find out how the protection of civilian object and armed members injured in armed conflicts is regulated according to international humanitarian law, and to examine the role of the International Criminal Court (ICC) in efforts to enforce the regulations on the protection of civilian and military objects against the actions of Israeli soldiers according to humanitarian law. This writing method uses normative legal research methods. The secondary legal materials used are the Hague Conventions of 1907, the Geneva Conventions of 1949 and the Additional Protocol I of 1977, and the Rome Statute of 1998. These three regulations are important references for upholding International Humanitarian Law (IHL) in both international and non-international armed conflicts. Because this still frequently occurs and many civilian objects become targets of war resulting in suffering for civilians and military personnel undergoing treatment. The International Criminal Court as part of the global justice system since 2002, has the authority to prosecute those who commit genocide, war crimes, and crimes against humanity as stipulated in the Rome Statute. Although Israel is not basically a party to the Rome Statute because it has not ratified it yet, the Prosecutor of the ICC who has a referral from the UN Security Council can bring charges against non-ratifying states.